Dynamics of paramagnetic metallofullerenes in carbon nanotube peapods. - Warner, J; Watt, A; Ge, L; Porfyrakis, K; Akachi, T; Okimoto, H; Ito, Y; Ardavan, A; Montanari, B; Jefferson, J; Harrison, N; Shinohara, H; et al. (2008)
We filled SWNTs with the paramagnetic fullerene Sc@C82 to form peapods. The interfullerene 1D packing distance measured using TEM is d = 1.1 +/- 0.02 nm. The Sc@C82 in SWNT peapods continuously rotated during the 2 s TEM exposure time, and we did not see the Sc atoms. However, Sc@C82 metallofullerenes in MWNT peapods have periods of fixed orientation, indicated by the brief observation of Sc atoms. La@C82 peapods were also prepared and their rotational behavior examined. The interfullerene 1D packing of both La@C82 and Sc@C82 peapods is identical and thus independent of the charge transfer state for these paramagnetic fullerenes. The La@C82 metallofullerenes in the peapods have fixed orientations for extended periods of time, up to 50 s in some cases. The La@C82 spontaneously rotates rapidly between fixed orientations.